A Full-Thickness Skin Graft In Women With Recurrent Basal Cell Carcinoma In The Right Infraorbital Region: One Case Report - Widyastuti, Zilpa; Mochtar, Moerbono; Mawardi, Prasetyadi (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Introduction: Basal cell carcinoma (BCC) is a malignancy of the skin that mainly occurs in skin that is frequently exposed to sunlight. The first choice of treatment for BCC is excision. Excision is usually followed by reconstruction, as in this case report using a full-thickness skin graft reconstruction technique. Case: A 32-year-old woman came with a complaint of a lump appeared on the bottom of her right eye since a few weeks ago. The patient had previously been diagnosed with BCC in the same location about 1 year ago. The conclusion from histopathological examination of the lesion is BCC. The chosen management are excision of the tumor and reconstruction using the full-thickness skin graft technique. Discussion: Basal cell carcinoma generally occurs on the face and affects elderly population, but recently it is often found in groups of young adults. The main environmental risk factor that plays a role in the development of BCC is ultraviolet exposure. Management of BCC is usually done with surgery such as excisional biopsy followed by reconstruction such as skin graft. Conclusion: Basal cell carcinoma is the most common skin cancer. Excisional biopsy is helpful in differentiating skin tumors, inflammatory processes, and other dermal lesions. Skin grafts are an option when primary closure or flap repair are deemed unsuitable. Keywords: Basal cell carcinoma, fullthickness skin graft, infraorbita.